Vasopressin V(1a) Receptors Regulate Cerebral Aquaporin 1 after Traumatic Brain Injury - Rauen, Katrin (J Neurotrauma, 2020)
Brain edema formation contributes to secondary brain damage and unfavorable outcome after traumatic brain injury (TBI). Aquaporins (AQP), highly selective water channels, are involved in the formation of post-trauma brain edema; however, their regulation is largely unknown. Because vasopressin receptors are involved in AQP-mediated water transport in the kidney and inhibition of V(1a) receptors reduces post-trauma brain edema formation, we hypothesize that cerebral AQPs may be regulated by V(1a) receptors. Cerebral Aqp1 and Aqp4 messenger ribonucleic acid (mRNA) and AQP1 and AQP4 protein levels were quantified in wild-type and V(1a) receptor knockout (V(1a)(-/-)) mice before and 15 min, 1, 3, 6, 12, or 24 h after experimental TBI by controlled cortical impact. In non-traumatized mice, we found AQP1 and AQP4 expression in cortical neurons and astrocytes, respectively. Experimental TBI had no effect on Aqp4 mRNA or AQP4 protein expression, but increased Aqp1 mRNA (p < 0.05) and AQP1 protein expression (p < 0.05) in both hemispheres. The Aqp1 mRNA and AQP1 protein regulation was blunted in V(1a) receptor knockout mice. The V(1a) receptors regulate cerebral AQP1 expression after experimental TBI, thereby unraveling the molecular mechanism by which these receptors may mediate brain edema formation after TBI.